Rates of publication of FCPS dissertations in international and national peer-review journals among residents at AKUH; A cross sectional review of 15 years - Ainulakbar Mughal; Syed Akbar Abbas; Abdul Basit Shah Vargad; Muhammad Wasif; Soubia Akhtar; Ayesha Abbasi (Journal of the Pakistan Medical Association, 2022)
Objective: To see the rate of publication of postgraduate residents' dissertation. Method: The single-centre retrospective cross-sectional study was conducted at the Aga Khan University Hospital, Karachi, and comprised research publications from the residents of the departments of Surgery and Medicine who graduated between 2005 and 2020. The surgical subspecialties included Otolaryngology, Ophthalmology, Dentistry, General Surgery, Orthopaedics, Paediatric Surgery, Urology, Plastic Surgery and Cardiovascular Surgery. Data comprised demographics, current institution, current designation, information on dissertation/paper publication, topic of study, year of completion of dissertation, input from the research department, delay in exam due to incomplete dissertation and whether the paper got published in national or international journal. Data was analysed using SPSS 21. Results: Of the 103 subjects, 70(68%) were males and 33(32%) were females, while 73(70.8%) belonged to surgical specialties and 30(29.2%) were from non-surgical specialties. Of the 22(22.9%) who were able to convert, 12(54.5%) publications were carried by national peer-reviewed journals, while 10(45.4%) were carried by international journals; 9(40.9%) unpaid peer review journals and 13(59.1%) paid journals. Delay in exam due to incomplete dissertation was faced by only 16(16.6%) candidates. Conclusion: The rate of publication for resident dissertation was found to be low. Continuous...